La Monarchie adaptative. Le consensus monarchiste du libéralisme espagnol dans la crise de 1848 - Pedro Díaz Marín (Cahiers de Civilisation Espagnole Contemporaine)
The events of 1848, which significantly affected the configuration of European society and politics, had their echo in Spain. The insurrections that occurred in various parts of the country had repercussions on its political evolution, as they led to the emergence of the different conceptions that the various liberal currents had of the Monarchy. From 1848, the discrepancies between a more conservative and immobile liberalism, represented by the Moderate party, and another with a more transformative sign, linked to the Progressive Party, from whose left the nucleus of the Democrats broke off, became more evident. Despite these differences, Spanish liberalism managed to forge a consensus around the defense of the Monarchy, which favored its survival until 1868, by adapting to an increasingly exclusive and authoritarian political context.